2012
DOI: 10.1089/end.2012.0067
|View full text |Cite
|
Sign up to set email alerts
|

The Powerful Impact of Double-Layered Posterior Rhabdosphincter Reconstruction on Early Recovery of Urinary Continence After Robot-Assisted Radical Prostatectomy

Abstract: The Rocco double-layered PR and attempted NS and not surgeon experience were the significant independent predictive factors of early recovery of urinary continence after RARP. NS procedures positively influenced early recovery of urinary continence only when they were applied with the PR technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Finally, of the 22 studies defined eligible for the qualitative analysis, one was excluded because of a lack of standardised reporting of the continence recovery outcome (Fig. ), leaving 21 studies .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, of the 22 studies defined eligible for the qualitative analysis, one was excluded because of a lack of standardised reporting of the continence recovery outcome (Fig. ), leaving 21 studies .…”
Section: Resultsmentioning
confidence: 99%
“…We initiated posterior rhabdosphincter reconstruction in case 28. Details of our technique have been previously reported . The anterior reconstruction technique was initiated in case 12 and randomly used during RARP, in which the ligated DVC and the anterior muscle layer of the bladder (2 cm away from the neck) were approximated to reduce tension of the anastomosis.…”
Section: Methodsmentioning
confidence: 99%
“…Details of our technique have been previously reported. 9 The anterior reconstruction technique was initiated in case 12 and randomly used during RARP, in which the ligated DVC and the anterior muscle layer of the bladder (2 cm away from the neck) were approximated to reduce tension of the anastomosis. The DVC was ligated initially, but after case 70, the DVC was first incised without ligation and thereafter, was ligated with a running suture.…”
Section: Technical Modification With Increasing Experiencementioning
confidence: 99%
“…Gondo et al . have recently reported that posterior reconstruction was significantly associated with early recovery of urinary continence 1 month after catheter removal in univariate analysis . Their multivariate logistic regression analysis also showed that posterior reconstruction and attempted nerve‐sparing were the only independent predictive factors of urinary continence recovery 1 month after catheter removal (OR 15.01, P = 0.0003; and OR 2.248, P = 0.0402, respectively).…”
Section: Intraoperative Techniques To Improve Outcomes For Early Retumentioning
confidence: 99%